(untitled) (Aporia, 2017)
In his influential essay "Two Dogmas of Empiricism," W. V. Quine attacks two "dogmas" that have "conditioned... modern empiricism" (2002, p.176). Rejecting these two dogmas leads Quine to make two further claims: he constructs a complex model of human belief states and asserts, "total science... is underdetermined by experience" (2002, p.191). Larry Laudan’s 1990 essay "Demystifying underdetermination" hopes to cast doubt upon the "broad implications that many writers... draw" (Laudan 1990, p.271) from Quine’s claims in "Two Dogmas." I first attempt to expound key components of Quine’s essay so that its relationship to Laudan’s criticism can be better understood; further, I attempt to show that although Laudan’s discussion of "Two Dogmas" successfully invalidates implications that have been drawn from the work, it ignores key aspects of the work itself, misleading the reader.